Efficacy of Carob Leaves and Pods in Reducing Cyclophosphamide-Induced Toxicity on Bone Marrow and Peripheral Blood Leukocytes: Pharmaceutical Science-Pharmacology & Toxicology, Pharmacognosy - Y. Abajy, Mohammad; Nayal, Ream; Alqubaji, Mahassen; Abdrabbo, Yara (International Journal of Life Science and Pharma Research, 2022)
Cyclophosphamide is one of the chemotherapeutics for cancer, however this drug has severe side effects in multiple organs and is a well-known mutagenic agent. In this work the protective activity of antioxidant-rich Carob (Ceratonia siliqua L.) pods and leaves extracts against cyclophosphamide induced genotoxicity was studied. Safety of these extracts was evaluated in acute and subacute toxicity tests at a dose of 1500 mg/kg/day in albino rats. Both extracts exhibited no mortality or significant changes in rats' general behavior. Moreover, organ weights and blood chemistry revealed no toxic effects of these extracts (p>0.05).The anti-mutagenic potential of carob pods and leaves extracts were evaluated using in vivo bone marrow chromosomal aberration and micronucleus assays and in vitro comet assay for peripheral blood white cells. Results showed that rats that were treated with cyclophosphamide along with carob pods had a significant decrease in chromosomal aberrations when compared with cyclophosphamide-treated rats (p<0.05). Pods extract also showed significant reduction in cyclophosphamide-induced DNA migration (p<0.05). There were also highly statistically significant differences in the means of micronuclei (MNs) in immature red blood cells between cyclophosphamide group and carob leaves group (p<0.01).It could be concluded that Carob extracts had protective effect against cyclophosphamide- induced genotoxicity and may be considered as anti-mutagenic agent after conducting more studies.